The Role of Teacher Training in Enhancing Engineering Education in Indonesian Classrooms - Mukh Khusnaini; Kartika, Rika; Hidayat, Yasysyar (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Teacher training plays a critical role in improving the quality of engineering education in Indonesia, particularly in preparing educators to meet the challenges of Industry 4.0. This study aims to analyze how teacher training contributes to enhancing instructional practices, teaching strategies, and student learning outcomes in technical education. Using a qualitative literature review approach, this research synthesizes findings from national and international studies published between 2010 and 2024 that focus on teacher professional development in vocational and engineering education. The analysis reveals that industry-oriented and continuous professional development programs significantly enhance teachers’ pedagogical innovation, digital technology integration, and ability to implement project-based and outcome-based learning. Such training enables teachers to shift from traditional lecture-based instruction toward collaborative and experiential learning models aligned with industrial needs. As a result, students demonstrate higher engagement, improved technical competence, and greater readiness for professional environments. However, disparities in training access, weak collaboration between industries and educational institutions, and limited digital infrastructure remain persistent challenges. The study recommends the adoption of dual-system, blended learning, and mentoring-based training models that integrate real industrial experiences into classroom practices. These models can help ensure sustainable teacher competency development and improve the alignment between education and industrial demands.